2021
DOI: 10.1039/d1fo01918j
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin A1 and its digestive products prevent acrylamide-induced intestinal barrier dysfunction via the MAPK-mediated MLCK pathway

Abstract: Procyanidins can alleviate small intestine damage induced by acrylamide (ACR). However, little is known about whether procyanidins after gastrointestinal digestion can prevent ACR-induced intestinal barrier damage and the possible mechanism....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…There are few studies on the effect of AA and OTA on the integrity of the intestinal barrier that we are aware of. Research reported that exposure to AA reduced the expression of TJ proteins in the Caco-2 intestinal cell line model [ 46 ]. Alizadeh et al [ 47 ] showed that OTA exposure down-regulated TJ protein expression levels in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies on the effect of AA and OTA on the integrity of the intestinal barrier that we are aware of. Research reported that exposure to AA reduced the expression of TJ proteins in the Caco-2 intestinal cell line model [ 46 ]. Alizadeh et al [ 47 ] showed that OTA exposure down-regulated TJ protein expression levels in Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used immunofluorescence staining to colocalize occludin and ZO-1 and determine their distributions in the Caco-2 cell monolayer. Some studies have shown that MLCK is the main pathway involved in TJ deletion and control of intestinal permeability . Therefore, to further explore the mechanism of the paracellular absorption of QMDDQ, it is crucial to investigate the regulatory relationship between MLCK and TJs.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that MLCK is the main pathway involved in TJ deletion and control of intestinal permeability. 40 Therefore, to further explore the mechanism of the paracellular absorption of QMDDQ, it is crucial to investigate the regulatory relationship between MLCK and TJs. We quantitatively analyzed the expression of TJs (ZO-1, occludin, and claudin-2) by Western blotting (Figure 6A), showing that the MLCK-specific inhibitor ML-7 significantly increased the expression of ZO-1 (control group: 1 ± 0.009, ML-7 group: 1.34 ± 0.08, P < 0.05) (Figure 6B) and occludin (control group: 1 ± 0.06, ML-7 group: 1.73 ± 0.08, P < 0.05) (Figure 6C), while QMDDQ significantly decreased the expression of ZO-1 (QMDQ group: 0.66 ± 0.04, P < 0.05) (Figure 6B) and occludin (QMDDQ group: 0.59 ± 0.08, P < 0.05) (Figure 6C).…”
Section: Qmddq Activates Mlck To Promote Intestinal Absorptionmentioning
confidence: 99%
“…Claudin/ZO-1 Signaling Pathway. Tight junction proteins-occludin, claudin, and ZO-1-are indispensable for maintaining the normal function of the gut barrier [17]. eir expression was examined in intestinal tissues.…”
Section: Calycosin Maintains Intestinal Mucosal Barrier Integrity Of ...mentioning
confidence: 99%